Do the Best Teachers Get the Best Ratings? - Kornell, Nate; Hausman, Hannah (Frontiers in Psychology, 2016)
We review recent studies that asked: Do college students learn relatively more from teachers whom they rate highly on student evaluation forms? Recent studies measured learning at two time points. When learning was measured with a test at the end of the course, the teachers who got the highest ratings were the ones who contributed the most to learning. But when learning was measured as performance in subsequent related courses, the teachers who had received relatively low ratings appeared to have been most effective. We speculate about why these effects occurred: Making a course difficult in productive ways may decrease ratings but enhance learning. Despite their limitations, we do not suggest abandoning student ratings, but do recommend that student evaluation scores should not be the sole basis for evaluating college teaching and they should be recognized for what they are.